Cultural Pragmatics of Politeness: The Role of Javanese Krama Inggil in Indonesian Academic Communication - Budi Purnomo (Journal of linguistics, culture and communication, 2025)
This study investigates the cultural pragmatics of politeness through the integration of Javanese krama inggil expressions in Indonesian academic communication. While most Central Javanese people are bilingual in Javanese and Indonesian, the use of highly respectful Javanese forms within formal Indonesian-language settings remains underexplored. This research aims to examine how Javanese krama inggil expressions are inserted into Indonesian discourse during academic meetings organized by the Higher Education Service Institute Region VI, Central Java. Ten recordings of meeting interactions were analyzed qualitatively to identify the lexical and contextual meanings, politeness levels, and acceptance levels of the inserted expressions. Questionnaire data from lecturers and administrative staff were also collected to assess their perceptions. The findings reveal that krama inggil expressions appear systematically across opening, main, and closing segments of meetings, serving as markers of deference, respect, and cultural identity. The majority of respondents rated these expressions as “polite” or “very polite,” and “acceptable” or “highly acceptable” within Indonesian academic contexts. The results suggest that incorporating local linguistic resources enriches communicative harmony, reinforces cultural values, and demonstrates how politeness strategies transcend linguistic boundaries in multilingual professional settings.